7-Eleven Inc. : the fine line between franchise independence and interdependence - Hunt, Terrell; Lee, Cindy; Pekoske, Charlotte; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
On June 17, 2013, federal agents from the Immigration and Customs Enforcement Agency (ICE) seized fourteen 7-Eleven franchised stores that were responsible for running what the authorities described as a "modern day plantation" ring. The owners of these franchises were suspected of recruiting more than 50 illegal immigrants, working those employees approximately 100 hours a week, siphoning their pay, and forcing them to live in "unregulated boarding houses." The case focuses on 7-Eleven Inc.'s response and how the company sought to distance itself from individual franchise holders.
Originally Published InHunt, T., Lee, C., Pekoske, C., & O'Rourke IV, J. S. (2019). 7-Eleven Inc.: The Fine Line Between Franchise Independence and Interdependence. 19-01. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; 7-Eleven Inc; Franchises (Retail trade) -- United States; Forced labor